Has COVID-19 affected regional mortality from acute coronary artery disease? (comparison of two periods of 2017-2019 and 2020-2022) - I. V. Samorodskaya; M. G. Bubnova; O. A. Akulova (Кардиоваскулярная терапия и профилактика, 2024)
Aim. To assess the changes of mortality from acute coronary artery disease (CAD) in the Russian regions during the coronavirus disease 2019 (COVID-19) pandemic in 2020-2022 in comparison with the prepandemic period (2017-2019).Material and methods. Rosstat data on the average annual population and mortality rate in one-year age groups for 82 regions Russian were used. In the brief Nomenclature of Causes of Death of Rosstat, the codes of the International Classification of Diseases, 10th revision (ICD-10) are grouped as follows: I21.0-9 (acute primary) myocardial infarction (MI), I22.0-9 (recurrent MI), I20, I24.1-9 (other types of acute coronary artery disease), U07.1 and U07.2 (coronavirus disease 2019 (COVID-19)). The regional average standardized mortality rates (SMR; M±SD) were calculated using the European population standard using the direct standardization method per 100 thousand population. Comparisons were made using the nonparametric Wilcoxon t-test (differences were considered significant at p<0,05).Results. A decrease in the regional average SMR (per 100 thousand population) in the pandemic compared to the pre-pandemic period was revealed: from the sum of all acute CAD types — from 51,24±31,98 to 50,21±33,38 and from repeated MI — from 7,65±5,42 to 4,80±4,84; increase in SMR from acute MI — from 24,00±10,1 to 25,57±11,55, from other acute CAD types — from 19,58±25,23 to 19,83±26,21. Significant regional variability was noted in both the dynamics of the SMR from three acute CAD types, as well as the minimum and maximum SMR. Only in 2 regions in the pandemic period there was an increase in SMR from each of the three acute CAD types compared to the pre-pandemic period. In 18 regions, there was a decrease in SMR from each of the three forms, and in the rest, multidirectional changes were noted. There was no correlation between SMR for COVID-19 and SMR for acute CAD (r=0,034; p=0,76).Conclusion. The COVID-19 pandemic did not have a significant impact on the regional average SMR from acute CAD. The significant decrease in SMR from recurrent MI is likely due to choice of the initial cause of death.